Spatial distribution patterns and driving factors of understory vegetation species diversity on northeastern Tibetan Plateau - Yanwen Hu; Jingyuan He; Beibei Chen; Senxuan Lin; Wennong Kuang; Xiuhai Zhao; Chunyu Zhang (Ecological Indicators)
Understory vegetation diversity plays a crucial role in stabilizing forest communities and shaping ecosystem structure and function. Understanding its geographic patterns and underlying mechanisms is essential. This study examined species richness and Shannon entropy of shrubs and herbs in understory layers of the northeastern Tibetan Plateau. Diversity indices in the shrub layer were positively correlated with latitude, displayed a U-shaped relationship with aspect, and negatively correlated with elevation. Topographical factor, particularly elevation, along with dissolved organic nitrogen (DON), significantly reduced shrub species richness (SD0) and Shannon entropy (SD1), while coefficient of variation of tree height (CVH) had a significantly positive impact. In contrast, herb layer diversity indices showed the opposite trends, with negative correlations to latitude and positive correlations with elevation. Herb species richness (HD0) and Shannon entropy (HD1) were primarily negatively influenced by latitude, number of stand stems (N) and CVH, while available potassium (AK) had a positive influence. These findings highlight the diverse impacts of environmental and biotic factors on understory diversity on the Tibetan Plateau, providing insights for more effective conservation strategies in alpine ecosystems.